A Monetary history of the United States, 1867-1960 - Friedman, Milton, 1912-2006; Schwartz, Anna J. (Anna Jacobson), 1915-2012 (Studies in business cycles ;, 1971)
Writing in the June 1965 issue of theEconomic Journal, Harry G. Johnson begins with a sentence seemingly calibrated to the scale of the book he set himself to review: "The long-awaited monetary history of the United States by Friedman and Schwartz is in every sense of the term a monumental scholarly achievement--monumental in its sheer bulk, monumental in the definitiveness of its treatment of innumerable issues, large and small ... monumental, above all, in the theoretical and statistical effort and ingenuity that have been brought to bear on the solution of complex and subtle economic issu